MULTIPLE ATTENUATION USING PREDICTIVE TAU-P DECONVOLUTION AND PARABOLIC RADON TRANSFORM - IHSAN RAMDANI (NIM : 12405014), AHMAD
Multiples is a seismic wave that reflected more that once before returns to the surface and recorded by receivers (1995. Uren, Norman). Multiples become problems in seismic section, because it tend to interfere primary reflection signals and can be mistaken for primary reflection events. Several method have been developed to attenuate multiples. Some of them are Predictive Tau-P Deconvolution and Parabolic Radon Transform. Predictive Tau-P Deconvolution (Tau-P Deconvolution in short) using transformation of seismic data from T-X (two way time-offset) domain into Tau-P (intercept time-ray parameter) domain. The predictive deconvolution are used in Tau-P domain and then the data are inverted back to T-X domain. Parabolic radon transform using transformation of seismic data from T-X (two way time-offset) domain into Tau-P (intercept time-moveout parameter) domain. The input for Parabolic Radon Transform are NMO corrected gather, and the transformation itself was done by using moveout correction parameter. In Radon domain, multiples are attenuated and the data after multiple attenuation are inverted back to T-X domain. In this final project, multiple attenuation using Predictive Tau-P Deconvolution and Parabolic Radon Transform was done to real 2D marine seismic data. Combination of these two method was success to attenuate long and short period multiples. As for the evaluation, Tau-P Deconvolution became less effective when attenuating short period multiples from dipping reflector.